PENDEKATAN KERNEL UNTUK SEBARAN TEMPERATUR DAN BAHAN PADA PERMUKAAN BOLA DUA DIMENSI - , rizki ilmianih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Temperature distribution on two dimensional sphere has been gained from diffution formulation using heat kernel estimation. The compactly sphere made the Ricci curved scalar became non-negative. As a concequence, the kernel satisfied LiYau estimation. Then, the obtained kernel equation was used to calculate the temperature and substance distribution by using three kind of sources: (1) the instantenious pointlike source, (2) periodically instaneous pointlike source, (3) the time dependet pointlike source. Heat distribution and diffusion which were plotted by using software of Mathematica showed there were differences of final temperature of that cases.